The role of the academic and political empowerment of women in economic, social and managerial empowerment: The case of Saudi Arabia - Maleeha Mohammed Zaaf Al-Qahtani; Tarek Tawfik Alkahteeb; Haider Mahmood; Manal Abdalla Zahed Abdalla; Thikkryat Jebril Obaid Talalah Qaralleh (Economies, 2020)
Women may be considered to have hidden, unutilized potential for the economy and society, if not utilized at their full capacity, i.e., with effective educational, social and political policies. Allowing women to participate fully in an economy may contribute to the sustainable development of the country in question. The empowerment of women may be accelerated if women are educated for this purpose; as a result, the political authorities in Saudi Arabia have proposed a comprehensive framework to empower women. The empowerment of women is essential in the academic sector to develop educational policies for women's capacity-building. The empowerment of women in the political process is also very important, so they can suggest appropriate policies, rules and laws that favor the empowerment of women in all sectors of the economy and society. The present research aims at testing the effects of academic and political empowerment on the economic, social and managerial empowerment of women, and opens a new horizon of debate in the practical and theoretical domain of female empowerment in Saudi Arabia. To this end, we utilized structural equation modeling due to the endogenous nature of relationships among the hypothesized variables. Perception-based data were collected on the political, academic, economic, social and managerial empowerment of women through a well-structured questionnaire. The data were collected during the period from October 2019 to January 2020 through a simple random sampling method. Then, we tested the direct effect of political empowerment, and its indirect effects through academic empowerment, on the economic, social and managerial empowerment of women. We found that political empowerment has a positive direct effect on economic and managerial empowerment, but an insignificant effect on social empowerment. Further, political empowerment has a positive direct effect on academic empowerment, which, in turn, has positive effects on economic, social and managerial female empowerment. Moreover, these indirect effects are found to be magnitudes larger than the direct effects of political empowerment. This study recommends improving the economic, social and political status of women through political and academic policies, to accelerate sustainable development.
Keywords: J16; B55; P26; 330; academic empowerment; economic empowerment; managerial empowerment; political empowerment; social empowerment; women’ s empowerment